Ulwaluko kwa Xhosa: young Xhosa men's lived experiences in the context of traditional male initiation - Siswana, Anele (Rhodes University, Faculty of Humanities, Department of Psychology, 2016)
This thesis explores the lived experiences of young amaXhosa men in relation to U!walukokwa Xhosa (traditional male initiation [TMI]) and its impact on their sense of masculinity. The conceptual framework of this study is located within African epistemology focusing on indigenous knowledge systems (IKS) in South Africa. The study aimed at enabling young amaXhosa men who had undergone TMI to reflect on their first-hand, personal accounts of Ulwa/ukokwa Xhosa and manhood. Six semistructured interviews and a follow up focus group discussion were held with 23-27 years old amaXhosa men residing in Joza Township in Grahamstown, Eastern Cape. Participants were identified through purposive sampling. The thesis reports on the following findings: (a) the significance of the place/location of initiation, and the guise of modernity; (b) feelings of anticipation experienced by the young men; (c) the theme on ubudoda(manhood) affirmation Ndiyindoda!; (d) the theme on the concealment of pain (perseverance); (e) the theme on respect for self and others and ubuntu;(f) Uzimelegeqe (independence and autonomy) and (g) social role and responsibility. The paper argues for the relevance of TMI as a significantrite of passage from boyhood to manhood among amaXhosa men.
Keywords: Uncatalogued